Learning Folklore Using English Language Teaching (ELT) Materials for Students - Cut Aja Puan Ellisafny (Culturalistics: Journal of Cultural, Literary, and Linguistic Studies, 2019)
Folklore is a medium in learning English because it has a context of stories that are close to language learners to make it easier to understand. This study aims to determine and correct errors in learning English based on folklore. The method used in this research is English Language learning using a descriptive and evaluation method. researchers use descriptive and evaluative methods. In the use of descriptive methods, the research process begins with drafting basic assumptions and thought rules to be used in research. In the evaluative method, the process of using this method is to evaluate the teaching materials in the use of folklore. The results obtained from this study are knowing weaknesses and errors in learning, especially writing, reading, and speaking to 20 students. Researchers also provide guidance to correct errors in writing, reading and speaking. Keywords: English Language Teaching (ELT), Folklore, Research and Development.